Organizational economics and health care markets. - Robinson, J C (2001)
As health policy emphasizes the use of private sector mechanisms to pursue public sector goals, health services research needs to develop stronger conceptual frameworks for the interpretation of empirical studies of health care markets and organizations. Organizational relationships should not be interpreted exclusively in terms of competition among providers of similar services but also in terms of relationships among providers of substitute and complementary services and in terms of upstream suppliers and downstream distributors. This article illustrates the potential applicability of transactions cost economics, agency theory, and organizational economics more broadly to horizontal and vertical markets in health care. Examples are derived from organizational integration between physicians and hospitals and organizational conversions from nonprofit to for-profit ownership.